Silicon-Organic Hybrid Photonic Devices in a Photonic Integrated Circuit Technology. (18th November 2019) - Steglich, Patrick; Mai, Christian; Mai, Andreas
Abstract : In this work, we present recent results on the hybrid integration of electro-optical organic materials in a photonic integrated circuit (PIC) technology. We review some of the identified challenges regarding process compatibility and present experimental results on the integration of organic materials in a PIC technology using a 0.25 μm SiGe BiCMOS pilotline. Here, we are focusing on electro-optical applications toward high-speed modulators with ultra-low energy consumption.